U UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS MENGGUNAKAN 3M (MELIPAT, MENGGUNTING, DAN MENEMPEL) PADA ANAK SEKOLAH DASAR KELAS AWAL: Application of the 3M Technique (Folding, Cutting, and Sticking) to Improve Fine Motor Skills in Early Grade Elementary School Students - saras, candrika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Fine motor skills are different for every child, some are slow and some are developmentally appropriate depending on the child's maturity level. A child's motor skills are considered delayed if they should be able to develop new skills at this age but are not showing any progress. Activities that can be done to improve fine motor skills in early childhood are very diverse, but the most effective activities for improving fine motor skills in early childhood are folding, cutting and cutting, as the activities of applying scissors and cutting are moving can small muscles. such as fingers and hands, as they are used for everyday activities such as writing and drawing. The aim of this research is to improve children's fine motor skills through 3M activities, namely folding, cutting and gluing, because children's fine motor skills need to be developed from an early age to improve hand muscles used in carrying out school Activities are needed. This research uses a qualitative descriptive analysis approach, which is a library research. The conclusion of this research is that the role of the teacher is very important as he acts as a motivator and innovator in the classroom. Therefore, teachers need to develop children's skills, especially eye and hand coordination skills, often referred to as fine motor skills. According to the researchers' observations, learning did not proceed as it should. Elementary school children in the first grades receive less incentive to improve fine motor skills.